Pengaruh Model Pembelajaran Problem Based Learning dan Motivasi Belajar Terhadap Hasil Belajar Ekonomi (Studi Kuasi Eksperimen pada Siswa SMA Negeri 27 Jakarta) - Fadiah Fadiah (Educational Journal, 2026)
This study aims to determine the effect of the Problem-Based Learning (PBL) model and learning motivation on the economics learning outcomes of 11th-grade students at SMA Negeri 27 Jakarta. This is a quantitative study employing a quasi-experimental approach, featuring non-randomly assigned control and experimental classes. The sample consisted of 72 students, with 36 students in the control group and 36 in the experimental group. Data on economics learning outcomes were collected via practice exercises, while learning motivation was measured using a questionnaire. The results indicate a difference in economics learning outcomes between students taught using the Problem-Based Learning model and those taught using conventional methods; specifically, the Problem-Based Learning model had a positive and significant effect on learning outcomes. Furthermore, differences in learning outcomes were observed between students with low learning motivation and those with high learning motivation. Finally, the study found a combined interaction effect between the two variables—the Problem-Based Learning model and learning motivation—on the economics learning outcomes of the 11th-grade students at SMA Negeri 27 Jakarta.